CuAl LDH/Rice Husk Biochar Composite for Enhanced Adsorptive Removal of Cationic Dye from Aqueous Solution - Neza Rahayu Palapa; Tarmizi Taher; Bakri Rio Rahayu; Risfidian Mohadi; Addy Rachmat; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The preparation of CuAl LDH and biochar (BC) composite derived from rice husk and its application as a low-cost adsorbent for enhanced adsorptive removal of malachite green has been studied. The composite was prepared by a one-step coprecipitation method and characterized by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), Brunauer-Emmett-Teller (BET), and Scanning Electron Microscopy - Energy Dispersive X-ray (SEM−EDX). The result indicated that CuAl LDH was successfully incorporated with the biochar that evidenced by the broadening of XRD peak at 2θ = 24° and the appearance of a new peak at 1095 cm−1 on the FTIR spectra. The BET surface area analysis revealed that CuAl/BC composite exhibited a larger surface area (200.9 m2/g) that the original CuAl LDH (46.2 m2/g). Surface morphological changes also confirmed by SEM image, which showed more aggregated particles. The result of the adsorption study indicated the composite material was efficient in removing malachite green with Langmuir maximum adsorption capacity of CuAl/BC reaching 470.96 mg/g, which is higher than the original CuAl LDH 59.523 mg/g. The thermodynamic analysis suggested that the adsorption of malachite green occurs spontaneously (ΔG < 0 at all tested temperature) and endothermic nature. Moreover, the CuAl/BC composite showed strong potential as a low-cost adsorbent for cationic dye removal since it showed not only a high adsorption capacity but also good reusability. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).